2017
DOI: 10.1136/bcr-2017-220125
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium phosphide poisoning with severe cardiac dysfunction and the role of digoxin

Abstract: Aluminium phosphide (ALP) is a common cause of suicidal poisoning in India where it is easily available and commonly known as 'rice tablet'. In rural areas of India, it is still used to protect rice and stored grains from rodents and pests. There is no specific antidote for phosphide poisoning and treatment involves meticulous supportive care. Ingestion can lead to severe cardiac suppression and cardiogenic shock. For patients poisoned with ALP who continue to have refractory shock with persistent myocardial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Some factors are known to improve the prognosis of ALP intoxication, which include younger age, ALP gas aspiration, drinking of ALP solution instead of tablet ingestion, vomiting following ingestion, and/or low-dose ingestion. On the other hand, some factors can worsen the prognosis of its intoxication, including hyperglycemia on admission, ingestion of fresh tablet, cardiac abnormality, especially VT, severe metabolic acidosis, cardiogenic shock and other types of shocks, electrolyte disturbances, other end-organ damages, and a need for mechanical ventilation [2,[4][5][6][7]. By induction of multi-organ failure, ALP kills its victims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors are known to improve the prognosis of ALP intoxication, which include younger age, ALP gas aspiration, drinking of ALP solution instead of tablet ingestion, vomiting following ingestion, and/or low-dose ingestion. On the other hand, some factors can worsen the prognosis of its intoxication, including hyperglycemia on admission, ingestion of fresh tablet, cardiac abnormality, especially VT, severe metabolic acidosis, cardiogenic shock and other types of shocks, electrolyte disturbances, other end-organ damages, and a need for mechanical ventilation [2,[4][5][6][7]. By induction of multi-organ failure, ALP kills its victims.…”
Section: Discussionmentioning
confidence: 99%
“…VT in these patients is treated by amiodarone and Magnesium Sulfate (MgSO4), but it is still known as an indicator of poor prognosis among ALP poisoned patients [5]. Several case report studies have indicated the successful cardioversion from VT to the sinus rhythm using MgSO4 and amiodarone [6]. Although using lidocaine could cardiovert patients with VT rhythm to sinus rhythm, in some other studies, it could not be cardioverted [7].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is based on exposure history, gastric aspirate analysis, gas chromatography study/mass spectrometry method, or on the presence of specific phosphine odor (smell of garlic or decaying fish). 1 , 2…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum phosphide (ALP) is commonly a suicidal agent in some countries; however, accidental poisoning is rare. 1 Myocardial damage occurs in 60% to 100% of cases of ALP intoxication. It can manifest as pericarditis or myocarditis, new-onset heart failure, subendocardial infarction, refractory hypotension, and shock.…”
Section: Introductionmentioning
confidence: 99%
“…Other articles spoke favorably about other antidotes, including triiodothyronine, acetyl-L-carnitine, glutathione, liothyronine, milrinone, Laurus nobilis L, vasopressin, sodium selenite, sulfate, N-acetylcysteine, 6-aminonicotinamide, boric acid, melatonin, vitamins C and E [10], selegiline [11], and whole blood transfusion [12]. Other articles reviewed the roles of digoxin [13], extracorporeal cardiopulmonary resuscitation [14], aortic balloon [15], and prophylactic amiodarone for symptomatic improvement in cardiac function [16]. In another article, the authors discussed the protective role of G6PD deficiency in wheat pill poisoning [17].…”
Section: Discussionmentioning
confidence: 99%